The unknown country [videorecording (DVD)] - Maltz, Morrisa; Gladstone, Lily; Gladstone, Lily; Shangreaux, Lainey Bearkiller; Shangreaux, Lainey Bearkiller; Taing, Vanara, 1979-; Shangreaux, Devin; Shangreaux, Jasmine Bearkiller; Lee, Raymond, 1987-; Whitman, Richard Ray (Music Box Films, 2023)
After a devastating loss, an unexpected invitation launches Tana on a solitary road trip through the Midwest, reconnecting with family, seeking closure, and making unexpected connections along the way.